Impact of spleen size and splenectomy on outcomes of allogeneic hematopoietic cell transplantation for myelofibrosis: A retrospective analysis by the chronic malignancies working party on behalf of European society for blood and marrow transplantation (EBMT). Issue 1 (27th October 2020) - Polverelli, Nicola; Mauff, Katya; Kröger, Nicolaus; Robin, Marie; Beelen, Dietrich; Beauvais, David; Chevallier, Patrice; Mohty, Mohamad; Passweg, Jakob; Rubio, Marie Thérèse; Maertens, Johan; Finke, Jürgen; et al.
Abstract: The role of spleen size and splenectomy for the prediction of post‐allogeneic hematopoietic stem cell transplant (allo‐HCT) outcome in myelofibrosis remains under debate. In EBMT registry, we identified a cohort of 1195 myelofibrosis patients transplanted between 2000‐2017 after either fludarabine‐busulfan or fludarabine‐melphalan regimens. Overall, splenectomy was performed in 202 (16.9%) patients and its use decreased over time (28.3% in 2000‐2009 vs 14.1% in 2010‐2017 period). By multivariate analysis, splenectomy was associated with less NRM (HR 0.64, 95% CI 0.44‐0.93, P = .018) but increased risk of relapse (HR 1.43, 95% CI 1.01‐2.02, P = .042), with no significant impact on OS (HR 0.86, 95% CI 0.67‐1.12, P = .274). However, in subset analysis comparing the impact of splenectomy vs specific spleen sizes, for patients with progressive disease, an improved survival was seen in splenectomised subjects compared to those patients with a palpable spleen length ≥ 15 cm (HR 0.44, 95% CI 0.28‐0.69, P < .001), caused by a significant reduction in NRM (HR 0.26, 95% CI 0.14‐0.49, P < .001), without significantly increased relapse risk (HR 1.47, 95% CI 0.87‐2.49, P = .147). Overall, despite the possible biases typical of retrospective cohorts, this study highlights the potential detrimental effect of massive splenomegaly in transplant outcome and supports the role of splenectomy for myelofibrosis patients with progressive disease and large splenomegaly.